Repair of topoisomerase I covalent complexes in the absence of the tyrosyl-DNA phosphodiesterase Tdp1 - Liu, Chunyan (National Academy of Sciences, 2002)
Accidental or drug-induced interruption of the breakage and reunion cycle of eukaryotic topoisomerase I (Top1) yields complexes in which the active site tyrosine of the enzyme is covalently linked to the 3′ end of broken DNA. The enzyme tyrosyl-DNA phosphodiesterase (Tdp1) hydrolyzes this protein-DNA link and thus functions in the repair of covalent complexes, but genetic studies in yeast show that alternative pathways of repair exist. Here, we have evaluated candidate genes for enzymes that might act in parallel to Tdp1 so as to generate free ends of DNA. Despite finding that the yeast Apn1 protein has a Tdp1-like biochemical activity, genetic inactivation of all known yeast apurinic endonucleases does not increase the sensitivity of a tdp1 mutant to direct induction of Top1 damage. In contrast, assays of growth in the presence of the Top1 poison camptothecin (CPT) indicate that the structure-specific nucleases dependent on RAD1 and MUS81 can contribute independently of TDP1 to repair, presumably by cutting off a segment of DNA along with the topoisomerase. However, cells in which all three enzymes are genetically inactivated are not as sensitive to the lethal effects of CPT as are cells defective in double-strand break repair. We show that the MRE11 gene is even more critical than the RAD52 gene for double-strand break repair of CPT lesions, and comparison of an mre11 mutant with a tdp1 rad1 mus81 triple mutant demonstrates that other enzymes complementary to Tdp1 remain to be discovered.